NiZnCoO4/CoWO4 hybrid composite with improved electrochemical performance for supercapacitor application. (15th August 2022) - Neiber, Rana R.; Kumar, Jai; Soomro, Razium Ali; Karkus, Selcan; Abo-Dief, Hala M.; Alanazi, Abdullah K.; Altalhia, Amal A.; El-Bahy, Zeinhom M.
Abstract: The inferior conductivity and structural durability are key issues in engineering suitable metal oxide-based hybrid electrodes for supercapacitor application. Herein, we propose using an in-situ route to couple Ni-Zn-Co trimetallic oxides (NZC) with CoWO4 (CWO) to construct an efficient hybrid composite electrode. The approach offers an intimate/compact interfacial arrangement with a better synergy of multi-atom conductivity, surface area, and numerous redox-active sites, resulting in superior electrochemical characteristics compared to its pristine counterparts. Hybrid composites with varying mass combination ratios were studied for enhanced electrochemical performance, where ZNC@CWO-10 realized a comparatively better capacitance of 370.9 F g −1 at 0.5 A g −1 with a capacitance retention value of 90% after 500 cycles. The corresponding ASC devise exhibited a high specific capacitance of 140 F g −1 at 0.5 A g −1 in the potential window of −1 to 0.8 V with maintained retention of 80% during 5000 cycles. The enhanced electrochemical characteristics were attributed to the improved composting strategy, allowing for synergism of ZNC and CoWO4 with superior interfacial arrangement paving the route towards excellent metal/metal oxide electrode material for supercapacitor applications. Highlights: In-situ growth of CWO4 over ZnNiCoO4 was engineered as an efficient hybrid electrode. The synergistic effect played a significant role in defining electrochemical assets of electrode. ZnNiCoO4 @CWO4 delivered an 30% high capacitance than its pristine counterparts. The ASC device shows high power and energy density.